PENGUKURAN INTENSI KONSUMEN TERHADAP PRODUK ELEKTRONIKA BERBASIS PEMASARAN HIJAU - Pratomo, Sigit Adhi; sri Nugroho, Arif Julianto; Jati, Agung Nugroho; Nugrahani, Cahaya; Tasari, Tasari; Haris, Abdul (Universitas Of Surakarta, 2024)
Electronic waste (e-waste) is currently a global issue which has a negative impact on the environment people and health. The negative impact has begun to spur the electronic industry in the World and in Indonesia to create environmentally friendly products and management of waste arrangement to be recycled. This study aims to analyze the effect of green marketing on intention decisions based on Zam-Zam electronic green product shop in Klaten City Central Java. The sample is 120 respondents of electronic product buyer consumers. The sampling technique is done by non random- purposive sampling. The variables used in the study include green product quality activities and green promotional improvement as an independent variable and green product purchasing intention as the dependent variable. Test of the statistics model done by SPSS 21. Model tests include the validity and reliability of questionnaire items, normality test, correlation coefficient test, multiple linear regression test, partial test (t test), simultaneous test (F test) and determination coefficient test (R2 test). The results of the study prove that the quality of green electronic products and green advertising have a positive and significant effect on the decision to intention electronic products at Zam-Zam shop in Klaten City